KESIAPSIAGAAN BENCANA PERKOTAAN DI SEKOLAH MENENGAH PERTAMA NEGERI 8 KOTA SERANG PROVINSI BANTEN - Riny Handayani (SEBA: Jurnal Pengabdian kepada Masyarakat, 2025)
Disaster Preparedness is a series of actions taken before a disaster occurs to reduce risk, minimize impact and ensure an effective response. Disaster preparedness is one of the stages in disaster management. disaster events that often occur in Serang City based on data obtained from the Serang City BPBD in 2024 are at least 166 floods, 6 landslides, 5 drowning events, 354 collapsed houses, 54 fallen trees and 13 fire events. The socialization activity was carried out at State Junior High School 8, Walantaka District, Serang City, and was attended by OSIS administrators with the aim of increasing knowledge related to disaster preparedness, especially in the school environment. Disaster preparedness socialization in the school environment is also an effort to increase the preparedness of school elements for potential disasters, especially those that occur in Walantaka District, Serang City. This activity is an activity at the pre-disaster stage and is very important because what has been prepared at this stage is capital in facing disasters and post-disasters. This socialization is carried out in the form of providing counseling and disaster education, especially for people living in areas prone to urban disasters. This is done in an effort to change the paradigm, increase knowledge and attitudes so that a resilient society is built, making people, especially school students, care about their environment so that the impact of disasters can be reduced. Capacity building for participants requires further steps, especially for disaster simulations that can be carried out routinely at least once a year. The local government in collaboration with all relevant stakeholders is expected to take the initiative by including disaster education in the school curriculum, in addition to providing guidance and steps to facilitate disaster management training in the school environment.Keywords: Disaster Preparedness, Urban, SMPN 8 Serang City